Enhancing basic computer network learning outcomes of vocational high school students by implementing a video-based learning model - Setyawan, Herlin; Sukardi, Sukardi; Diati, Lili Safitri; Fitri, Yolanda Idha; Ambiyar, Ambiyar (Universitas Negeri Padang, 2024)
Many students still achieved scores below the minimal completeness criteria when learning basic computer networks. This was because the teacher still uses traditional media, such as printed worksheets in the teaching process which made the learning boring and harder for students to comprehend what the teacher was teaching. Therefore, this research aimed to implement video-based learning within the educational process. This study employed a pre-experiment methodology by using a single pre- and post-test group. Thirty-three students majoring in computer and network engineering served as the research subjects. The paired sample t-test and N-gain score were the data analysis methods employed to examine the efficacy of the video-based instruction. The results demonstrated a significant improvement from students' knowledge before to that of after being engaged in video-based learning. Thus, it is possible to conclude that a video-based instruction can greatly enhance students' understanding on fundamental computer network science. According to the study's findings, the video-based learning ought to be incorporated into the curriculum of vocational education, particularly in the Department of Computer Network Engineering, to ensure that the students fully comprehend the subject matter and that the learning process runs smoothly.